Assessment of the application for renewal of the authorisation of Calsporin® (Bacillus velezensisDSM 15544) as a feed additive for weaned piglets. (13th November 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of Calsporin ® ( Bacillus velezensis DSM 15544) as a zootechnical additive for weaned piglets. The product under assessment is based on viable spores of a strain originally identified as Bacillus subtilis . During the course of the current assessment, the active agent has been reclassified as Bacillus velezensis DSM 15544. B. velezensis is considered suitable for the qualified presumption of safety (QPS) approach to safety assessment. The identity of the active agent was established and the compliance with the other qualifications confirmed. Therefore, B. velezensis DSM 15544 is presumed safe for the target species, consumers of products derived from animals fed the additive and the environment. Since no concerns are expected from the other components of the additive, Calsporin ® is also considered safe for the target species, consumers of products derived from animals fed the additive and the environment. The additive is not a dermal/eye irritant or a skin sensitiser but should be considered a respiratory sensitiser. The present application for renewal of the authorisation did not include a proposal for amending or supplementing the conditions of the original authorisation that would have an impact on the efficacy of the additive. Therefore, there was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.